Implementing the Panca Cinta Love-Based Curriculum to Foster Students' Ecological Awareness in Elementary Science Education - Nurul Makrifah; Nur Fauzi; Moh. Amiril Mukminin (Journal of Educational Management Research, 2026)
This study aims to describe the implementation of the Panca Cinta Love-Based Curriculum and examine students’ ecological awareness in science learning. A descriptive qualitative approach was employed, with data collected through observation, interviews, and documentation, and analyzed through data selection, reduction, and summarization. The findings reveal that the Panca Cinta Love-Based Curriculum was implemented effectively and contributed to the development of students’ ecological awareness, as reflected in their understanding of environmental issues, caring attitudes toward the environment, environmentally friendly behavior, critical thinking about ecological problems, and social responsibility for environmental conservation. These findings suggest that integrating love-based values into science learning can enhance students’ ecological awareness while fostering environmental responsibility and character development, making the Panca Cinta framework a promising approach to supporting sustainable education in elementary schools.